Interior of the mandapa of the Jain Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the interior of the mandapa (pillared hall) of the Jain Temple. The mandapa is astylar in plan meaning that the central portion does not contain any pillars. The pillars are lined along the corners of the mandapa. The entrance to the garbhagriha (sanctum sanctorum) is right in front of the main north-facing entrance to the temple. The west and east sides of the mandapa have relief transepts. The stone interiors of the temple are heavily damaged owing to a bat infestation.